It could happen to anyone why battered women stay - LaViolette, Alyce D.; Barnett, Ola W.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
Drawing on extensive research, this text provides a comprehensive examination of why women stay in abusive relationships and why they leave, explaining why women should not be blamed for their victimisation.
Previous ed.: 1993.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Abused women -- United States -- Case studies; Electronic books